Workplace generations in South Africa - De Beer, Craig Ross (My University, 2019)
As the ratio of Millennials in the workplace has continued to increase over the last twenty years, organisations across the world have been encouraged to tailor specific strategies to attract and retain top performing individuals within this cohort. However, these strategies have often been informed by theoretical arguments, while the empirical research to date reveals mixed findings. In addition, the traditional generational classifications have been principally based on American (U.S.), and to some degree European, historical characteristics. These western classifications of generations largely exclude aspects of culture, personal preferences, or agency inherent in non-western contexts. Therefore, it is unclear to what degree the adoption of the traditional generational classifications are useful in South African workplace contexts. Furthermore, despite the vast social and political differences between generations in South Africa, the inconsistency of findings in the generation-based literature at a local level also suggests that the generation-based strategies for recruitment, retention, reward, and promotion adopted by South African organisations should not be done so unquestioningly.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts (in the field of Organisation Psychology) Faculty of Humanities, University of the Witwatersrand, 2019
Keywords: Reproduction--South Africa; Career development--South Africa